Preparation of polypropylene/octadecane composite films and their use in the packaging of cherry tomatoes. Issue 41 (13th July 2016) - Kim, Dowan; Lim, Mijin; Seo, Jongchul
ABSTRACT: Polypropylene (PP)/octadecane (OD) composite films were prepared via twin‐screw extrusion, and their chemical, morphological, thermal, and surface properties and oxygen and water vapor permeabilities were analyzed as functions of the OD content and temperature. OD was dispersed well in the PP matrix, and two phases (i.e., the PP and OD portions) were present in the PP/OD composite films. When the temperature was increased from 10 to 30 °C, both the oxygen transmittance rate and the water vapor transmittance rate of the PP/OD composite films increased sharply because of the influence of the OD content. These results were related to the temperature‐dependent changes in the morphological structure, such as changes in the the tortuous paths and crystallinity in the composite films because of the addition of OD. In the storage test, the PP/OD (83:17) composite films continuously controlled the gas concentration of the headspace and protected against environmental factors; this reduced the enzymatic activity and led to higher quality cherry tomatoes compared to the case when the pure PP and MP33000 films were used. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44087. Abstract :